PELVIC SOLITARY FIBROUS TUMOR, HISTORICALLY CLASSIFIED AS HEMANGIOPERICYTOMA, PRESENTING WITH VENOUS COMPRESSION AND PELVIC CONGESTION: A CASE REPORT - Svilar, Dejan; Djosic, Jovana; Djuric, Andjela; Stojanovic, Bojan (Halo 194 Scientific Journal of Emergency Medicine, 2026)
Introduction: Solitary fibrous tumor is a rare fibroblastic mesenchymal neoplasm previously classified with hemangiopericytoma. Although it can occur at nearly any anatomical site, pelvic involvement is uncommon and symptoms usually appear late because they result from progressive mass effect.Case presentation: A 69-year-old man presented with abdominal pain, progressive right lower limb swelling, and paresthesia. Laboratory findings showed mild anemia, elevated fibrinogen, and mildly increased C-reactive protein, while serum tumor markers remained normal. Multidetector computed tomography demonstrated a large lobulated hypervascular abdominopelvic mass with heterogeneous enhancement and central necrosis. Computed-tomographic angiography revealed compression of the right iliac vein, femoral venous dilatation, and marked pelvic venous congestion. Doppler ultrasonography confirmed abnormal venous flow without definite thrombosis.Conclusion: (SFT) represents a rare but clinically significant diagnosis in the differential evaluation of large hypervascular pelvic masses. A multidisciplinary approach is essential for optimal treatment planning, while surgical resection remains the primary therapeutic modality.
Keywords: solitary fibrous tumor; hemangiopericytoma; pelvis; multidetector computed tomography; Color Doppler ultrasonography.